(untitled) (Palíndromo, 2013)
This article presents a study on the disfigurement in art. The underlying theme of the text is the attempt of human beings in understanding themselves based on the image of their face. It formulates questions about the portrait, figure, contours and appropriate contexts linking the appearance, identity and the shape’s intelligibility. Évelyne Grossman, George Didi-Huberman, Rolan de Calan and Pierre Bergounioux are some of the interlocutors who prompt the questionings.